The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1210/jcem.87.5.8513
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in the Sisters of Women with Polycystic Ovary Syndrome: Association with Hyperandrogenemia Rather Than Menstrual Irregularity

Abstract: This study was performed to determine whether the sisters of women with polycystic ovary syndrome (PCOS) have evidence for insulin resistance. Three hundred and thirty-six women with PCOS, 307 sisters of these probands, and 47 control women were studied. The sisters were grouped by phenotypes: PCOS [hyperandrogenemia (HA) with chronic oligo-or amenorrhea, n = 39], HA with regular menses (n = 36), unaffected (UA; n = 122), and unknown (n = 110). The analyses were adjusted for age and body mass index. PCOS and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 169 publications
(82 citation statements)
references
References 63 publications
5
70
2
5
Order By: Relevance
“…Three mothers did not report menstrual history and were assigned unknown menstrual status and excluded from all analyses based on menstrual history. Hyperandrogenemia in mothers was defined by the same criteria used in the probands with PCOS (11,17). We did not record self-reported hirsutism because we have found that such self-assessments are unreliable (unpublished observations), an observation that has also been confirmed by other investigators (36).…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…Three mothers did not report menstrual history and were assigned unknown menstrual status and excluded from all analyses based on menstrual history. Hyperandrogenemia in mothers was defined by the same criteria used in the probands with PCOS (11,17). We did not record self-reported hirsutism because we have found that such self-assessments are unreliable (unpublished observations), an observation that has also been confirmed by other investigators (36).…”
Section: Methodsmentioning
confidence: 87%
“…1). When hyperandrogenemia was defined categorically (11,17), 3% of mothers fulfilled the National Institute of Child Health and Human Development diagnostic criteria for PCOS (18), and 6% of mothers had hyperandrogenemia with a history of regular menses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations